2022
DOI: 10.3126/gaze.v13i1.42081
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tourism on Economic Growth of Nepal: Is Tourism-Led Growth Hypothesis Valid for Nepal?

Abstract: A voluminous study is available on tourism-growth nexus as tourism industry received considerable attention as a potential source of economic growth. This paper empirically examines the impact of tourism on economic growth of Nepal by using time series data of 1976-2020 and applying autoregressive distributed lag (ARDL) approach. Real GDP was used as proxy measure of economic growth, which was the outcome variable whereas the variable of interest was tourism receipts. Foreign aid, total volume of trade and rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…As a result of the analysis, it was found that international tourism revenues, foreign trade and total workforce affect economic growth in a statistically positive and significant way. These results have been reported in the literature as follows: Çetintaş and Barışık (2009), Gül and Kamacı (2012), Seghir et al, (2015), Korkmaz and Aydın (2015), Değer and Recepoğlu (2016), Hamdan (2016), Ohlan (2017), Yazdi et al (2017), Shahbaz et al (2018), Eroz et al (2020), Rasool et al (2021, Durmuş et al (2021), Bhattarai and Karmacharya (2022) have similar results.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
“…As a result of the analysis, it was found that international tourism revenues, foreign trade and total workforce affect economic growth in a statistically positive and significant way. These results have been reported in the literature as follows: Çetintaş and Barışık (2009), Gül and Kamacı (2012), Seghir et al, (2015), Korkmaz and Aydın (2015), Değer and Recepoğlu (2016), Hamdan (2016), Ohlan (2017), Yazdi et al (2017), Shahbaz et al (2018), Eroz et al (2020), Rasool et al (2021, Durmuş et al (2021), Bhattarai and Karmacharya (2022) have similar results.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
“…This result is line with Paudyal (2012) who claimed that tourist arrivals show that tourism has impacted positively on the Nepalese economy. Our result is also consistent with the results of Karki (2018), Jaiswal (2018), andNepal et al (2019) whereas inconsistent with of Bhattarai and Karmacharya (2022). Tourist arrivals contribute to economic development through the employment opportunity, government income (through taxes), and infrastructure development.…”
Section: Ardl (Long-run and Short-run) Approachsupporting
confidence: 87%
“…From the ARDL model and Granger causality tests, the authors judged that a 1% increase in GDP would result in a 1.56% rise in tourism; the contribution of tourist arrivals to GDP was relatively small at less than 4% and therefore does not significantly contribute to economic growth. Using time series data from 1976 to 2020 using an autoregressive distributed lag (ARDL) technique, Bhattarai and Karmacharya (2022) empirically investigated the influence of tourism on Nepal's economic growth. The result of ARDL model shows that tourism has no significant impact on economic growth of Nepal in both short-run and long-run.…”
Section: Tourism and Economic Growth Nexus In Nepalmentioning
confidence: 99%
“…weather, are also major draws (MFFA, 2022). Due to the abundance of natural and historical monuments, Nepal has great potential for developing tourism (Acharya & Halpenny, 2013;Bhattarai & Karmacharya, 2022).…”
Section: Introductionmentioning
confidence: 99%